B*2-a*3+1=0

Simple and best practice solution for B*2-a*3+1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for B*2-a*3+1=0 equation:


Simplifying
B * 2 + -1a * 3 + 1 = 0

Reorder the terms for easier multiplication:
2B + -1a * 3 + 1 = 0

Reorder the terms for easier multiplication:
2B + -1 * 3a + 1 = 0

Multiply -1 * 3
2B + -3a + 1 = 0

Reorder the terms:
1 + 2B + -3a = 0

Solving
1 + 2B + -3a = 0

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + 2B + -1 + -3a = 0 + -1

Reorder the terms:
1 + -1 + 2B + -3a = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 2B + -3a = 0 + -1
2B + -3a = 0 + -1

Combine like terms: 0 + -1 = -1
2B + -3a = -1

Add '3a' to each side of the equation.
2B + -3a + 3a = -1 + 3a

Combine like terms: -3a + 3a = 0
2B + 0 = -1 + 3a
2B = -1 + 3a

Divide each side by '2'.
B = -0.5 + 1.5a

Simplifying
B = -0.5 + 1.5a

See similar equations:

| 11x+1y=3 | | 3m+9=5m-5 | | x+2*64=6*64 | | 10(x+1)=5x+25 | | 2(w+l)=2w+2l | | 3(x+20)=15 | | x/6-x/7=3/7 | | (a-16)/5=29 | | a-16/5=29 | | a-16/5=-8 | | 12x-18=10x | | 7(v-4)=14 | | (a-16)/5=-8 | | -6u+3=-3(u-3) | | 6sen(A)-3=0 | | -3m=-4+8 | | a^2+11a+10=0 | | (6d+5)(d-8)= | | X/5=12/35 | | 28x^2-94x+60=0 | | 28x^2-94x+30=0 | | (3c^2+2c-1)(2c^2+c+9)= | | xy-2a-2x+ay= | | 3x^2+9x-1= | | (3c+2c-1)(2c^2+c+9)= | | 3a^2+6a+2=0 | | 3u^3+15u^2-87u-315=0 | | -10.8/-2= | | 4+3(3a+3)=5 | | 0.01x-1.5=0.009 | | 3.14*R^2*12=258.75 | | pi*r^2*12=258.75 |

Equations solver categories